2008
DOI: 10.1177/1362361307089517
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perceptions of communication with professionals during the diagnosis of autism

Abstract: In order to obtain the views of parents concerning their perceptions of the process of getting a diagnosis of an autistic spectrum disorder (ASD) for their child, 15 focus groups were conducted across a range of locations in England. These groups were split into parents of preschool-, primary- and secondary-aged children who had recently received an ASD diagnosis. At the time of diagnosis, most of the parents wished for a quicker and easier process. In particular, they would prefer the procedure to have a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
182
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(200 citation statements)
references
References 20 publications
11
182
1
6
Order By: Relevance
“…(1) Time taken to get a diagnosis: Several studies have found that a quicker journey through the diagnostic process results in increased satisfaction (Howlin & Moore, 1997;Osbourne & Reed, 2008;Siklos & Kerns, 2007;Smith, Chung, & Vostanis, 1994). It was hypothesised that those who experienced fewer delays between first seeking help and receving a diagnosis would be more satisfied.…”
Section: Adult Asd Diagnosis Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Time taken to get a diagnosis: Several studies have found that a quicker journey through the diagnostic process results in increased satisfaction (Howlin & Moore, 1997;Osbourne & Reed, 2008;Siklos & Kerns, 2007;Smith, Chung, & Vostanis, 1994). It was hypothesised that those who experienced fewer delays between first seeking help and receving a diagnosis would be more satisfied.…”
Section: Adult Asd Diagnosis Surveymentioning
confidence: 99%
“…3) The quality of information given at diagnosis: Research has shown that parents who are well-informed about the nature of ASDs, including how these may affect their child and where they can go for help, are more likely to be satisfied with the care they receive (Hasnat & Graves, 2000;Mansell & Morris, 2004;Osbourne & Reed, 2008). It was predicted that overall satisfaction would be greatest amongst those who rated the provison of information at diagnosis highly.…”
Section: Adult Asd Diagnosis Survey 7 (mentioning
confidence: 99%
“…Particular frustration relates to the lengthy delays associated with the process (1,10). These delays can postpone access to services and limit confidence in their clinicians' ability to help, during or after diagnosis (1,10,11,12). This, in turn, has led to calls for increased training on autism for GPs and other frontline professionals (13).…”
Section: How This Fits Inmentioning
confidence: 99%
“…Given the significant challenges these respondents' reported, it is unsurprising that they expressed a desire for more autism training. Currently, GPs appear to rely on their personal connections of autism (through family members, friends, colleagues) as a source of tacit 12 knowledge -which may provide a more visceral and more nuanced appreciation of the realities of autism (14,18). An overreliance on subjective, personal knowledge could, however, afford a narrow, idiosyncratic view of what autism is, potentially causing clinicians to miss the signs in some individuals, potentially leading to disparities in healthcare provision (39).…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Examination of parents' health information sources reveal that parents use a large number and wide variety of sources such as newsletters, conferences, meetings, magazines and television [8,11]. Parents' information seeking patterns have been found to change over time and relate to their children's immediate needs and concerns [8,12,13] Lastly, parents gauge the quality of the information that is given to them and desire guidance when seeking health information independently [7,11,12,14]. These studies suggest that parents engage in many activities related to accessing information however how parents actually use health information in caring for their children or in working with health providers or teachers is unknown.…”
Section: Introductionmentioning
confidence: 99%